Excess employment, media coverage and corporate valuation: Labour Contract Law in China*. Issue 1 (2nd January 2016) - Yang, Deming; Zhao, Can
Abstract: Previous research has found that firms' excess employment will reduce corporate valuation as well as lead to a series of negative economic consequences. However, these studies cannot explain why the excess employment would lead to a series of negative economic consequences. Using the exogenous event of the promulgation of the new Labour Contract Law ('the Act') enacted in 2007 in China, this paper finds that an increase in excess employment will reduce the valuation of firms. With the promulgation and implementation of the Labour Contract Law, the negative correlation between excess employment and corporate valuation is significantly strengthened, which shows that excess employment has a more serious negative economic impact after the law is implemented. It has been shown elsewhere that labour costs have increased since the implementation of the Act. This paper reveals that the mechanism relating excess employment to negative economic consequences is that excess employment leads to increasing labour costs rather than reducing enterprise productivity. Furthermore, we present evidence that media coverage significantly reduces the negative correlation between excess employment and the valuation of the firm, which extends the information intermediary theory of media.